Contribution of Pro-inflammatory Cytokine Signaling within Midbrain Periaqueductal Gray to Pain Sensitivity in Parkinson’s Disease via GABAergic Pathway - Zhuang, Xianbo; Chen, Yanxiu; Zhuang, Xianpeng; Chen, Tuanzhi; Xing, Tao; Wang, Weifei; Yang, Xiafeng (Frontiers in Neurology, 2016)
Background/Aims: Hypersensitive pain response is often observed in patients with Parkinson's disease (PD); however, the mechanisms responsible for hyperalgesia are not well understood. Chronic neuroinflammation is one of the hallmarks of PD pathophysiology. Since the midbrain periaqueductal gray (PAG) is an important component of the descending inhibitory pathway controlling on central pain transmission, we examined the role for pro-inflammatory cytokines (PICs) system of PAG in regulating exaggerated pain evoked by PD. Methods: We used a rat model of PD to perform the experimental protocols. PD was induced by microinjection of 6-hydroxydopamine to lesion the left medial forebrain bundle. Pain responses to mechanical and thermal stimulation were first examined in control rats and PD rats. Then, ELISA and Western Blot analysis were used to determine PIC levels and their receptors expression. Results: Protein expression of IL-1β, IL-6 and TNF-α receptors (namely, IL-1R, IL-6R and TNFR subtype TNFR1) in the plasma membrane PAG of PD rats was upregulated, whereas the total expression of PIC receptors was not significantly altered. The ratio of membrane protein and total protein (IL-1R, IL-6R and TNFR1) was 1.48±0.15, 1.59±0.18 and 1.67±0.16 in PAG of PD rats (P < 0.05 vs. their respective controls). This was accompanied with increases of PICs of PAG, and decreases of GABA (623±21 ng/mg in control rats and 418±18 ng/mg in PD rats; P < 0.05 vs. control rats) and withdrawal thresholds to mechanical and thermal stimuli. Our data further showed that the concentrations of GABA and withdrawal thresholds were largely restored by blocking those PIC receptors in PAG of PD rats. Stimulation of GABA receptors in PAG of PD rats also blunted a decrease in withdrawal thresholds. Conclusions: Our data suggest that upregulation of the membrane PIC receptor in the PAG of PD rats is likely to impair the descending inhibitory pathways in regulating pain transmission and thereby plays a role in the development of hypersensitive pain response in PD.